2016
DOI: 10.3847/0004-637x/821/1/47
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Geometric Probabilities of Multi-Transiting Exoplanetary Systems From Corbits

Abstract: NASA's Kepler Space Telescope has successfully discovered thousands of exoplanet candidates using the transit method, including hundreds of stars with multiple transiting planets. In order to estimate the frequency of these valuable systems, it is essential to account for the unique geometric probabilities of detecting multiple transiting extrasolar planets around the same parent star. In order to improve on previous studies that used numerical methods, we have constructed an efficient, semi-analytical algorit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 54 publications
2
62
0
Order By: Relevance
“…First, we generate 10 4 systems randomly oriented in space for each simulated system; planets with impact parameters b < 1 are said to be transiting. We compared this method to Brakensiek & Ragozzine (2016)'s CORBITS and found that it produced consistent results.…”
Section: Comparison To Kepler Samplementioning
confidence: 93%
“…First, we generate 10 4 systems randomly oriented in space for each simulated system; planets with impact parameters b < 1 are said to be transiting. We compared this method to Brakensiek & Ragozzine (2016)'s CORBITS and found that it produced consistent results.…”
Section: Comparison To Kepler Samplementioning
confidence: 93%
“…Above planet system generating processes assume the planets are randomly paired. In order to better match the observed period ratio (pr; Fabrycky et al 2014;Brakensiek & Ragozzine 2016) and radius ratio (rr) distributions (Ciardi et al 2013;Weiss et al 2018), we further adjust the orbit ratios and rrs of the generated planet systems. Before the adjustment, we first debias the observed pr and rr distributions.…”
Section: Adjusting Period Ratios and Radius Ratiosmentioning
confidence: 99%
“…Before the adjustment, we first debias the observed pr and rr distributions. For each observed adjacent tranet pair, we use the CORBITS algorithms (Brakensiek & Ragozzine 2016) to calculate the probability of detecting the outer tranet given that the inner one is detected. The inverse of the probability is adopted as the weight of the tranet pair.…”
Section: Adjusting Period Ratios and Radius Ratiosmentioning
confidence: 99%
“…We use CORBITS (Brakensiek & Ragozzine 2016) to simulate random observations of all the systems. CORBITS computes the probability that any particular group of planets can be observed to transit in a multiple planet systems.…”
Section: Eccentricities and Inclinations Of Super-earthsmentioning
confidence: 99%